TiO2-N/Polystyrene photocatalyst-combined Corona Plasma Treatment for Methylene Blue Degradation - Kusumandari Kusumandari; Ahmad Qusnudin; Teguh Endah Saraswati; Davit Dhruv (ALCHEMY Jurnal Penelitian Kimia, 2024)
This study employed the corona plasma method combined with TiO2-N/PS photocatalyst to degrade dye pollutants. The plasma reactor consisted of two needle-shaped stainless steel electrodes connected to a voltage of 8 kV. Methylene blue (MB) solution was used as a model pollutant with varied initial concentrations of 10, 50, and 100 ppm. The degradation efficiency was evaluated based on the absorbance of the degraded MB solution measured using a UV-Vis spectrophotometer. The results exhibited that the longer plasma treatment duration caused the absorbance value of the degraded MB to decrease, and then the MB degradation efficiency increased. MB-10 demonstrated a maximum degradation efficiency of 99.40% after plasma treatment for 30 minutes. Meanwhile, MB-50 and MB-100 reached maximum degradation efficiencies of 95.29 and 86.55% efficiency after plasma treatment for 60 minutes. The greater initial MB concentration caused the longer degradation process. Furthermore, the results revealed no increase in degradation efficiency due to the addition of TiO2-N/PS photocatalyst into the plasma treatment. The degradation efficiencies of MB-10, MB-50, and MB-100 under TiO2-N/PS-combined plasma treatment for 30 min were 94.48, 81.57, and 5.22%, respectively. This suggests the possibility that the UV light generated during the plasma process cannot activate the TiO2-N/PS photocatalyst.